2015
DOI: 10.1093/humrep/dev286
|View full text |Cite
|
Sign up to set email alerts
|

Paracervical block as pain treatment during second-trimester medical termination of pregnancy: an RCT with bupivacaine versus sodium chloride

Abstract: 29 May 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…17 Seven studies reported results from medical TOP (Figure 2; see Tables 1 and Table S1) among 453 participants hailing from Europe (five studies), Canada (one study) and Thailand (one study). 17,[19][20][21][22] The mean gestational age ranged from 16 to 22 weeks. Indications for TOP were described in six studies: in one, all TOPs were performed for fetal indications; 17 in another study, 80% were performed for fetal indications; 22 in three studies, fewer than half of the TOPs were performed for fetal indications; 19,21,24 and one study reported that all TOPs were 'indicated,' but did not specify those indications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Seven studies reported results from medical TOP (Figure 2; see Tables 1 and Table S1) among 453 participants hailing from Europe (five studies), Canada (one study) and Thailand (one study). 17,[19][20][21][22] The mean gestational age ranged from 16 to 22 weeks. Indications for TOP were described in six studies: in one, all TOPs were performed for fetal indications; 17 in another study, 80% were performed for fetal indications; 22 in three studies, fewer than half of the TOPs were performed for fetal indications; 19,21,24 and one study reported that all TOPs were 'indicated,' but did not specify those indications.…”
Section: Resultsmentioning
confidence: 99%
“…20 TOP was induced with mifepristone plus misoprostol in two studies, 19,21 misoprostol alone was used in three studies, 20,23,24 and gemeprost was used in two studies. 17,22 To report women's pain, six studies used an 11-point visual analogue scale (VAS), 17,[19][20][21][22]24 and one used an 11-point verbal scale; 23 two studies reported participant satisfaction with pain management using a visual or verbal scale. 22,23 Five studies reported the need for additional opioid pain medications for the participants beyond those of the study interventions; 17,[19][20][21]24 in contrast, studies using regional analgesia reported the overall consumption of pain medications or the need for additional anxiolytic medication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When presented with this opportunity, their decisions are based on rational information and fears related to the procedure, including fear of pain (Kanstrup, Mäkelä, & Hauskov Graungaard, ). Indeed, those who undergo medical or surgical abortion are at risk of intense physical pain (Andersson, Benson, Christensson, & Gemzell‐Danielsson, ; Andersson, Christensson, & Gemzell‐Danielsson, ; Jackson & Kapp, ; Lafarge, Mitchell, & Fox, ; Renner, Jensen, Nichols, & Edelman, ) and sufficient pain management is emphasized in the literature (Bygdeman et al, ; Dennis, Blanchard, & Bessenaar, ; Royal College of Obstetricians & Gynaecologists, ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who undergo medically induced second-trimester abortions experience both emotional distress and physical pain before, during, and after the abortion [15-19]. To deal with their difficult situation, they have a great need for information and support [15-18].…”
Section: Introductionmentioning
confidence: 99%